2007
DOI: 10.1007/s00429-007-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical analysis of afferent projections to the medial prefrontal cortex in the rat

Abstract: The medial prefrontal cortex (mPFC) has been associated with diverse functions including attentional processes, visceromotor activity, decision making, goal directed behavior, and working memory. Using retrograde tracing techniques, we examined, compared, and contrasted afferent projections to the four divisions of the mPFC in the rat: the medial (frontal) agranular (AGm), anterior cingulate (AC), prelimbic (PL), and infralimbic (IL) cortices. Each division of the mPFC receives a unique set of afferent project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

72
1,096
7
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,178 publications
(1,184 citation statements)
references
References 183 publications
72
1,096
7
9
Order By: Relevance
“…This finding is consistent with the known connectivity distinctions between IL layers (Gabbott et al, 2005). Moreover, dopaminergic projections from the VTA to the PFC synapse predominantly in layer V (Hoover and Vertes, 2007), providing evidence for a potential dopaminergic role in extinction retrieval, even in the absence of pharmacological manipulation. We found that while IL-BLA circuit activity did not correlate with freezing in VEH-treated animals, SKF treatment resulted in diverging correlations between layer V activation and freezing behavior in PRO vs EMD animals.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with the known connectivity distinctions between IL layers (Gabbott et al, 2005). Moreover, dopaminergic projections from the VTA to the PFC synapse predominantly in layer V (Hoover and Vertes, 2007), providing evidence for a potential dopaminergic role in extinction retrieval, even in the absence of pharmacological manipulation. We found that while IL-BLA circuit activity did not correlate with freezing in VEH-treated animals, SKF treatment resulted in diverging correlations between layer V activation and freezing behavior in PRO vs EMD animals.…”
Section: Discussionsupporting
confidence: 87%
“…The layer V pyramidal neurons in ACd integrate widespread inputs from various brain regions (Hoover and Vertes, 2007) and project to multiple subcortical areas, including striatum, amygdala, dorsal raphe, and spinal cord (Gabbott et al, 2005), to facilitate emotional expression, motor coordination, and temporal organization of behavior. In adult mice with early-life stressful experiences and vehicle treatment, mPFC-dependent cognition, including certain aspects of attention (reflected by the percentage of same arm returns) and temporal order memory, was markedly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Projections originating in the perirhinal cortex and terminating in other cortical areas include the anterior cingulate, prelimbic, infralimbic, frontal, piriform, visual and parietal cortices (Saper, 1982;Naber et al, 1997;Burwell and Amaral, 1998a,b;Haberly, 2001;Hoover and Vertes, 2007;Agster and Burwell, 2009). Unlike the afferent projections of the perirhinal cortex, its efferents all involve both areas 35 and 36, albeit with some weighting towards one or the other in some cases (Burwell and Amaral, 1998a;McIntyre et al, 1996;Delatour and Witter, 2002;Agster and Burwell, 2009).…”
Section: Cortical Projectionsmentioning
confidence: 99%
“…There are a number of return projections from the perirhinal cortex to the medial prefrontal cortex (Hoover and Vertes, 2007). Specifically, the perirhinal cortex projects to the anterior cingulate, prelimbic and infralimbic cortices Agster and Burwell, 2009).…”
Section: Cortical Projectionsmentioning
confidence: 99%